Expanding urolithiasis treatment: comparison of super pulsed thulium laser and holmium:YAG laser for ureteral stone management - Qinghua Gan; Jun Li; Gaoqiang Zhai; Bangfeng Liu; Yan Qin; Shuting Tan; Wei Wang; Qinsong Zeng (European Journal of Medical Research)
Abstract Objectives The purpose of this review is to compare the effectiveness of SuperPulsed thulium fiber laser (SP TFL) and holmium:yttrium–aluminum–garnet (Ho:YAG) laser in lithotripsy, with the aim of evaluating the differences between the two in key indicators, such as lithotripsy efficiency and safety, and providing reference for clinical selection of better lithotripsy methods. Methods By searching multiple authoritative medical databases (PubMed, Embase, and Web of Science databases) and including the results of relevant clinical studies and laboratory studies, the indexes involving SP TFL and Ho:YAG lasers in the included literature were analyzed. Results We found a total of 24 relevant pieces of literature. The laser parameters, such as ablation efficiency, ablation speed, operative time, dust quality, retropulsion, visibility, temperature safety, and stone-free rate, were compared between laboratory studies and clinical outcomes. Preclinical studies have shown that SP TFL has a higher rate of stone ablation, a weaker retropulsion and a lower risk of fiber breakage. The results of clinical studies showed that the two methods were comparable in the ablation rate, laser time and operative time, stone-free rate and complication. SP TFL offered better endoscopic view quality and less retropulsion. Conclusions While the Ho:YAG laser remains the primary choice for endoscopic laser lithotripsy, the emergence of SP TFL offers a promising new option for the minimally invasive treatment of urinary calculi. Parameter range, retropulsion effect, laser fiber adaptability, and overall system performance demand comprehensive attention. SP TFL has a relatively short clinical application history, and further research is necessary to fully explore its long-term advantages, clinical significance, and possible limitations.